Effects of Early Changes in Blood Pressure During Intravenous Thrombolysis on the Prognosis of Acute Ischemic Stroke Patients - Zhong-Xiu Wang; Zhong-Xiu Wang; Zhong-Xiu Wang; Chao Wang; Chao Wang; Chao Wang; Peng Zhang; Peng Zhang; Peng Zhang; Yang Qu; Yang Qu; Yang Qu; et al. (Frontiers in Aging Neuroscience, 2020)
Background: Intravenous thrombolysis (IVT) therapy is currently one of the best medical treatments available for patients with acute ischemic stroke. Studies have shown that blood pressure (BP) changes in patients treated with IVT are significantly correlated with prognosis.Objective: Our study aimed to determine the relationship between BP changes during recombinant tissue plasminogen activator (rt-PA) infusion and the 3-month prognosis evaluated using the modified Rankin Scale (mRS) and determine the factors influencing BP changes during rt-PA infusion.Methods: Consecutive patients who were treated with IVT and admitted to our stroke center between May 2015 and October 2017 were analyzed retrospectively. Patients were divided into two groups according to their 3-month prognosis status: patients with mRS ≤ 2 were defined as “favorable outcome group” and those with mRS ≥ 3 as “unfavorable outcome group”. First, the factors affecting prognosis after thrombolysis were analyzed. Second, we analyzed the relationship between BP and the prognosis. BP was taken before and at regular intervals of 15 min during the rt-PA infusion (1 h). The average value of BP during thrombolysis was calculated and compared to the baseline BP. BP decrease was defined as the difference between the baseline BP and the average BP, provided it was greater than 0 mmHg. Third, univariate and multivariate analyses were performed to identify factors that may contribute to BP decrease.Results: In total, 458 patients were included. Patients with a lower baseline National Institute of Health Stroke Scale (NIHSS) score (8.25 ± 5.57 vs. 13.51 ± 7.42, P < 0.001), a higher Alberta Stroke Program Early CT Score (ASPECTS; 8.65 ± 1.82 vs. 8.13 ± 2.00, P = 0.005), decreased BP during thrombolysis (69.4% vs. 59.8%, P = 0.037), and steady BP (SD < 10 mmHg) were more likely to have a favorable outcome (73.9% vs. 60.6%, P = 0.019). High baseline BP (OR > 1), hypertension history (OR < 1), and baseline ASPECTS (OR > 1) were independent factors of BP change during thrombolysis.Conclusion: Patients with decreased or steady BP during thrombolysis were more likely to have a favorable outcome. Baseline ASPECTS, baseline NIHSS score, and hypertension history influenced BP changes during thrombolysis.